Una lealtad entre ruinas : epistolario Azaą-Esplá : 1939-1940 / Pedro L. Angosto, Julia Puig (eds.) - Esplá, CarlosAngosto, Pedro L.Puig, Julia; Azaą, Manuel (1880-1940) (Publicaciones)
Bibliografía: p. 189-196